2005
DOI: 10.1128/jvi.79.14.8764-8772.2005
|View full text |Cite
|
Sign up to set email alerts
|

RING-H2 Protein WSSV249 from White Spot Syndrome Virus Sequesters a Shrimp Ubiquitin-Conjugating Enzyme, PvUbc, for Viral Pathogenesis

Abstract: Modification of proteins by ubiquitin is essential for numerous cellular processes. The RING-H2 finger motif has been implicated in ubiquitin-conjugating enzyme (E2)-dependent ubiquitination. Four proteins, WSSV199, WSSV222, WSSV249, and WSSV403, from white spot syndrome virus (WSSV) contain the RING-H2 motif. Here we report that WSSV249 physically interacts with a shrimp ubiquitin-conjugating enzyme, PvUbc, and mediates ubiquitination through its RING-H2 motif in the presence of E1 and PvUbc. Mutations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 63 publications
0
51
0
Order By: Relevance
“…Recent research on WSSV structure using proteomic methods has revealed that its structural proteins have increased in number to 39 (Tsai et al 2004). Now, research activities have begun to focus on the protein-protein interactions between the shrimp and virus, between shrimp proteins, and between virus proteins (Lu & Kwang 2004, Tonganunt et al 2005, Wang et al 2005, Xie & Yang 2005. According to previous studies by Tsai et al (2004Tsai et al ( , 2006, VP53A encoded by WSSV gene wssv067 is an envelope protein.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on WSSV structure using proteomic methods has revealed that its structural proteins have increased in number to 39 (Tsai et al 2004). Now, research activities have begun to focus on the protein-protein interactions between the shrimp and virus, between shrimp proteins, and between virus proteins (Lu & Kwang 2004, Tonganunt et al 2005, Wang et al 2005, Xie & Yang 2005. According to previous studies by Tsai et al (2004Tsai et al ( , 2006, VP53A encoded by WSSV gene wssv067 is an envelope protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge of viral nonstructural proteins and the host cellular response during WSSV infection remains poor. To date, only a few nonstructural proteins, encoded by highly conserved gene sequences, such as DNA polymerase (9), ribonucleotide reductase (27), and others (14,16,18,27,28,47), have been confirmed by traditional gene cloning and immunoassays. Differential expression of host proteins was mainly investigated at the mRNA level using cDNA microarrays and expressed sequence tags (11,12,17,36,39,44).…”
mentioning
confidence: 99%
“…The E3 ligase activity of WSSV277 is involved in regulation of antiapoptosis by ubiquitin-mediated degradation of tumor suppressor-like (TSL) protein (12), and it is required for efficient WSSV replication (14). WSSV304 serves as a ubiquitin ligase E3 to sequester a shrimp ubiquitin-conjugating enzyme, Penaeus vannamei Ubc (PvUbc), for viral pathogenesis (31). WSSV462, which has E3 ligase function, is a regulator for the latency state of WSSV (13).…”
mentioning
confidence: 99%
“…AAL89172.1), and WSSV462 (GenBank accession no. AAL89330.1), contain the RING-H2 motifs and may function as the E3 ligases (31). The E3 ligase activity of WSSV277 is involved in regulation of antiapoptosis by ubiquitin-mediated degradation of tumor suppressor-like (TSL) protein (12), and it is required for efficient WSSV replication (14).…”
mentioning
confidence: 99%